THE DEVELOPMENT OF LEARNING MATERIALS PjBL-STEM TO IMPROVE STUDENTS’ SCIENTIFIC LITERACY SKILLS - Siti Maghfirah; Muhammad Syukri; A Halim; Nurazidawati Mohammad Arsad (Balai Besar Guru Penggerak Jawa Timur, 2023)
This study aims to develop the learning materials based on the STEM approach through the PjBL model that is feasible used to improve students’ scientific literacy in physics learning. The study is a development study using the ADDIE model which consists of five stages of development, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were the students of grade 11th at SMA Negeri 5 Banda Aceh in the academic year 2019/2020. This study in the implementation stage used an experimental research design (quasi-experimental design) in which the model used was non-equivalent control group design by utilizing research instruments such as the questionnaire, validation questionnaire, and scientific literacy skills question test. The post-test results of students’ scientific literacy skills were then tested by using a t-test to investigate the differences between the experiment and control class. Based on the results of the study, the learning materials developed was feasibly used to improve students’ scientific literacy skill. AbstrakPenelitian ini bertujuan untuk mengembangkan perangkat pembelajaran berbasis pendekatan STEM melalui model PjBL yang layak digunakan untuk meningkatkan literasi sains siswa dalam pembelajaran fisika. Penelitian ini merupakan penelitian pengembangan dengan menggunakan model ADDIE yang terdiri dari lima tahap pengembangan, yaitu Analysis, Design, Development, Implementation, and Evaluation. Subjek penelitian ini adalah siswa kelas XI SMA Negeri 5 Banda Aceh. Uji lapangan pada tahap implementation menggunakan desaign penelitian eksperimen (quasi experimental design) model yang digunakan adalah non-equaivalent control group design. Instrumen penelitain berupa angket validasi, angket respon guru dan peserta didik serta soal tes kemampuan literasi sains. Hasil posttest kemampuan literasi sains peserta didik kemudian diuji menggunakan uji t untuk melihat perbedaan antara kelas eksperimen dan kelas kontrol. Berdasarkan hasil penelitian diketahui bahwa perangkat pembelajaran yang dikembangkan layak digunakan untuk meningkatkan kemampuan literasi sains peserta didik.